Anatomic and Radiographic Safe Zone for Posterior Malleolar Screw Placement. (December 2021) - Williams, Caroline; Momenzadeh, Kaveh; Michalski, Max; Kwon, John Y.; Nazarian, Ara; Miller, Christopher P.
Background: The most appropriate treatment and management of posterior malleolar fractures (PMFs) lacks consensus. Indirect reduction and fixation with posterior to anterior (PA) screw shows promise by avoiding the risks associated with direct reduction or indirect anterior to posterior approaches. Some authors have raised concerns about potential risk to nearby structures with the PA technique, including hardware prominence into the syndesmosis. This study highlights use of the posteromedial vertical syndesmotic line (PVSL) as a fluoroscopic landmark, helping surgeons avoid intrasyndesmotic placement. Study aims are to evaluate PVSL correspondence with posterior border of the incisura tibialis and to define a safe zone between this line and flexor hallucis longus tendon. Methods: Indirect PA screw placement was completed on 10 cadaveric specimens, followed by fluoroscopy in mortise and lateral views. Dissection was performed to assess screw placement relative to the posteromedial border of the syndesmosis. The posterior border of the syndesmosis was marked with a radiopaque wire. Repeat imaging was completed to validate the fluoroscopic PVSL is representative of the posteromedial border of the tibial incisura. Results: On dissection, 9 out of 10 cadavers had accurate screw placement with no penetration into the syndesmosis. Corresponding imaging showed the screw head to be medial to the marker on mortise view. For the specimen with penetration into the syndesmosis, imaging confirmed that the screw head was lateral to the marker on mortise views. The radiopaque marker correlated with the PVSL for all specimens when comparing anatomic to radiographic findings. A radiographic safe zone is defined for the PA screw 12 mm medial to the PVSL to ensure no iatrogenic injury to the flexor hallucis longus tendon. Conclusion: This study demonstrated that a posterior incisura tibialis fluoroscopic landmark is unambiguous in localizing the posterior syndesmotic border and that screws medial to this line are safely out of the syndesmosis, while screws placed lateral are either in or at risk of intrasyndesmotic placement. A safe zone is defined for screw placement. Clinical Relevance: This article describes a radiographic and clinical safe zone for fixation and hardware placement during open reduction internal fixation (ORIF) of PMFs. This information will assist surgeons in avoiding intrasyndesmotic hardware placement as well as injury to deep soft tissue structures.